Macro Indicators of Crime Rates in Central Java Province - Annisa Eka Zakiyah; Rifki Khoirudin (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to analyze the influence of the Human Development Index (HDI), population, Open Unemployment Rate (OUR), and economic growth on the crime rate in Central Java Province from 2018 to 2024. This study uses a quantitative method with a panel data regression approach that combines time series and cross-sectional data from districts and cities in Central Java Province. The analytical model used is the Fixed Effect Model (FEM). The data used are secondary data obtained from the Central Statistics Agency (Badan Pusat Statistik/BPS). The results of the study show that the Human Development Index (HDI), population size, and the Open Unemployment Rate (OUR) have a positive and significant effect on the crime rate in Central Java Province. Meanwhile, economic growth has a positive but insignificant effect on the crime rate. Increases in HDI, population, and the open unemployment rate tend to be followed by a rise in crime due to socio-economic pressures, urbanisation, population density, and the weakening of social control in society. On the other hand, economic growth has not been able to fully reduce crime because the benefits of economic development have not been distributed equally across the community. Thus, it is necessary to distribute development more equitably, expand employment opportunities, and strengthen social supervision in order to reduce the crime rate in Central Java Province.